The impact of gender on emotional reactions, perceived susceptibility and perceived knowledge about COVID-19 among the Israeli public - Levkovich, Inbar (Int Health, 2021)
BACKGROUND: The current COVID-19 outbreak is seriously affecting the lives and health of people across the globe. While gender remains a key determinant of health, attempts to address the gendered dimensions of health face complex challenges. METHODS: In a cross-sectional study 482 participants (men=237, women=245) completed questionnaires on precautionary behaviour, perceived knowledge about COVID-19 risk factors, emotional reactions toward COVID-19 and perceived susceptibility. We examined gender differences in perceived knowledge about COVID-19 risk factors, healthy behaviours, threat perceptions and emotional responses, as well as the role of gender as a moderating factor. RESULTS: Women reported higher levels of precautionary behaviour (t(475)=3.91, p<0.001) and more negative emotional reactions toward COVID-19 (t(475)=6.07, p<0.001). No gender differences emerged in perceived susceptibility or knowledge about COVID-19. The multiple regression model is significant and explains 30% of the variance in precautionary behaviour, which was found to be higher among women and older participants, those with higher perceived knowledge about COVID-19 risk factors and those with higher emotional reactions. Gender exhibited a significant moderating role in the relationship between perceived knowledge and precautionary behaviour (B=0.16, SE=0.07, β=0.13, p=0.02, 95% CI 0.03 to 0.30). CONCLUSION: Women exhibited higher levels of precautionary behaviour and emotional responses.